Penilaian dan Evaluasi Pembelajaran Filsafat di Kampus Stisip Syamsul’ulum - Endin Nasrudin; Ridhwanullah Husain Al-Fawwaz; Azmi Abdulhakim; Muhamad Hilman Abdurahman; Alwi Muhammad Syawali (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
Philosophy learning has a strategic role in shaping students' critical, reflective, and rational thinking skills. However, the main challenge faced in this learning process is to determine assessment and evaluation methods that are in accordance with the character of philosophy that are abstract and argumentative. This study aims to describe the method, assessment, and evaluation of philosophy learning based on the results of an in-depth interview with STISIP lecturer Syamsul Ulum. The research approach used is qualitative with data collection techniques through in-depth interviews, so that a comprehensive picture of philosophy learning practices in higher education is obtained. The results of the study show that discussion methods, case studies, and critical reflection are the most effective approaches in improving the quality of philosophy learning. The assessment is more focused on the student's thinking process, not solely on the final result, while the evaluation is directed at changing the way of thinking and the intellectual maturity of the students. These findings confirm that philosophy learning is not only oriented towards mastery of the material, but also on the formation of a critical, reflective, and ethical mindset that is an important provision for students in dealing with the complexities of academic and social life. Thus, philosophy learning plays a role as a means of intellectual development as well as student morals.